FOG INDEX ON TEXTBOOKS OF INDONESIAN SUBJECT FOR CLASS X OF SENIOR HIGH SCHOOL IN STANDARD BASED CURRICULUM (SBC) AND CURRICULUM 2013 (A STUDY OF LEGIBILITY AND FEASIBILITY TEXTBOOKS) - Forta Gyawaji F; Kundharu Saddhono; , Edy Tri Sulistyo (Proceeding of International Conference on Art, Language, and Culture, 2017)
This research aims to describe and explain the readability and feasibility of the text in the textbook of Indonesian subject for class X of senior high school in standard based curriculum (SBC) and curriculum 2013. This research is a qualitative descriptive study using fog index as a formulation to calculate the readability aspect. The data of this research are taken from Indonesian subject in standard based curriculum and 2013 curriculum. The data collection technique is taken using documentation. The research data validity is measured using source triangulation .The data were analyzed using interactive data analysis model. The results of the research are (1) the readability of the text books of Indonesian subject for class X of senior high school in standard based curriculum (SBC) is categorized as the readability that easy to understand (2) the readability of the text books of Indonesian subject for class X of senior high school in curriculum 2013 is categorized as the readability that easy to understand; (3) The differences appear not in term of readability. Instead, they are on  the number and types of the texts that are used;(4) the textbook of Indonesian subject for class X in senior high school in standard based curriculum (SBC) is feasible, because it contains various types of text, meaning that it concerns with science and knowledge gained by reader.